Given DE is
"6y^2dx-x(2x^3+y)dy=0" After rearranging the above equation ,we can write
"\\frac{dx}{dy}-\\frac{x}{6y}=\\frac{x^4}{3y^2}\\\\\n\\implies -\\frac{3\\frac{dx}{dy}}{x^4}+\\frac{1}{2yx^3}=-\\frac{1}{y^2}" Put
"v=\\frac{1}{x^3}\\implies \\frac{dv}{dy}= -\\frac{3\\frac{dx}{dy}}{x^4}" Thus, we get
"\\frac{dv}{dy}+\\frac{1}{2y}v=-\\frac{1}{y^2}"
Hence, Integrating Factor is
"I.F=e^{\\int 1\/2ydy}=\\sqrt{y}" So it follows
"\\frac{d}{dy}(\\sqrt{y}v)=-y^{-3\/2}\\\\\n\\implies \\sqrt{y}v=-\\int y^{-3\/2}dy=2y^{-1\/2}+C_1\\\\\n\\implies v=C_1y^{-1\/2}+2y^{-1}\\\\\n\\implies \\frac{1}{x^3}=C_1y^{-1\/2}+2y^{-1}\\\\" After simplification we get,
"y{\\left(x \\right)} = \\frac{3 C_{1} \\sqrt{x^{9} \\left(9 C_{1}^{2} x^{3} + 8\\right)}}{2} + \\frac{x^{3} \\left(9 C_{1}^{2} x^{3} + 4\\right)}{2}\\\\\ny{\\left(x \\right)} = - \\frac{3 C_{1} \\sqrt{x^{9} \\left(9 C_{1}^{2} x^{3} + 8\\right)}}{2} + \\frac{x^{3} \\left(9 C_{1}^{2} x^{3} + 4\\right)}{2}"
Comments
Leave a comment